Keindahan dalam Kesederhanaan Wayang Krucil Wiloso : Sebuah Kajian Estetika Wabi Sabi - Arizal, Fariza Wahyu (LPPM STIKI Malang, 2025)
Wayang Krucil Wiloso Wiloso is one of the traditional Javanese art forms that developed in Wagir, Malang. This puppet, which originates from the story of the spread of Islam and also tells the story of Panji Asmorobangun and also the story of the menak in the spread of Islam. This puppet not only functions as entertainment but also as a means of education and the spread of moral values and local culture. This research examines the aesthetics of Wabi Sabi in Wayang design. Wayang Krucil Wiloso is different from other puppets, such as the use of contrasting colors, expressive body proportions, and simple ornaments, Wayang Krucil Wiloso still maintains traditional Javanese values and symbolism. When studied from the perspective of Wabi Sabi's eastern aesthetics, the traditional elements in Wayang Krucil Wiloso become an aesthetic study of beauty in simplicity to analyze the simple yet attractive visual appearance without losing its identity and characteristics. This research uses a descriptive qualitative method through observation, interviews, and literature study to understand the aesthetics of Wabi Sabi in Wayang Krucil Wiloso. The result is that Wayang Krucil Wiloso Wiloso, although appearing in simplicity and far from the splendor of puppets in general, can still perform its main functions, namely as entertainment, as a medium of education, moral messengers and also as a means of preaching and spreading Islam in East Java.